La politique nationale de réconciliation et de relocalisation des populations déplacées dans le Liban d’après-guerre - Dima de Clerck (L’Année du Maghreb)
The 16-year Lebanese War resulted in “sectarian cleansing” in many areas of the country leading to heavy population displacements. These displacements deeply affected the society and the economy in Lebanon. National demographic distribution has been altered, many villages have been emptied, and many regions and sectors of the economy have remained underdeveloped. For the displaced populations to resume their lives in their hometowns in a war aftermath curbed by a general amnesty Law, it was necessary to develop a national returnee strategy (NRS). Such a policy on a nation-wide scale could only be elaborated and implemented by the state, since it required important financial resources, specific legislation and even security measures. A ministry and a fund for the displaced were created in 1992 to ensure the return of all displaced people in Lebanon. The state returnee policy in southern Mount Lebanon, where several massacres had taken place in 1983, claimed to prioritize reconciliation between Christians and Druze to prevent resorting to, or being victim of reprisal. Thirty years after its launching, the reconciliation process failed to achieve many of its goals. Many took advantage of its resources for personal political and electoral benefits. The broader goals of the “pacification” and a sectarian rather than individual rationale have fuelled further sectarianism and fed into national-level power struggles. In addition, the process left little room for victims’ personal grieving through testimony and memory. This article looks at the failure of Lebanon’s state reconciliation policy to encourage displaced populations to return to their home villages and to promote a durable pacification.